1994
DOI: 10.1086/187423
|View full text |Cite
|
Sign up to set email alerts
|

Measurements of anisotropy in the cosmic microwave background radiation at 0.5 deg angular scales near the star gamma ursae minoris

Abstract: We present results from a four frequency observation of a 6° x 0°.6 strip of the sky centered near the star Gamma Ursae Minoris during the fourth flight of the Millimeter-wave Anisotropy eXperiment (MAX). The observation was made with a 1°.4 peak-to-peak sinusoidal chop in all bands. The FWHM beam sizes were 0°.55 ± 0°.05 at 3.5 cm -1 and 0°.75 ± 0°.05 at 6, 9, and 14 cm -1 . During this observation significant correlated structure was observed at 3.5, 6 and 9 cm -1 with amplitudes similar to those observed in… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

1995
1995
2016
2016

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(11 citation statements)
references
References 13 publications
(21 reference statements)
1
9
0
Order By: Relevance
“…The discovery of the anisotropy in the cosmic microwave background (CMB) by the COBE satellite (Smoot et al 1992;Bennet et al 1992) and its subsequent confirmation (Ganga et al 1993) at large angular scales (greater than 7 • ) has been followed by positive detections of anisotropies in the microwave sky at intermediate angular scales by a number of other experiments (De Benardis et al 1994;Devlin et al 1994;Dragovan et al 1994;Gundersen et al 1995;Gutierrez et al 1995) and upper limits at smaller angular scales (Meyers, Readhead, & Lawrence 1993;Tucker et al 1993). In order to reject foreground contamination, most of these experiments observe the sky over a range of frequencies.…”
Section: Introductionmentioning
confidence: 99%
“…The discovery of the anisotropy in the cosmic microwave background (CMB) by the COBE satellite (Smoot et al 1992;Bennet et al 1992) and its subsequent confirmation (Ganga et al 1993) at large angular scales (greater than 7 • ) has been followed by positive detections of anisotropies in the microwave sky at intermediate angular scales by a number of other experiments (De Benardis et al 1994;Devlin et al 1994;Dragovan et al 1994;Gundersen et al 1995;Gutierrez et al 1995) and upper limits at smaller angular scales (Meyers, Readhead, & Lawrence 1993;Tucker et al 1993). In order to reject foreground contamination, most of these experiments observe the sky over a range of frequencies.…”
Section: Introductionmentioning
confidence: 99%
“…Constrained by the measured level of anisotropy on large angular scales (Bennett et al 1994, Ganga et al 1993, different models predict varying levels of anisotropy on smaller scales. Several observing teams (Cheng et al 1994, de Bernardis et al 1994, Devlin et al 1994, Gundersen et al 1995, Netterfield et al 1995 including our own have reported detections of anisotropy on angular scales near 1 • . Improvements in these measurements should help discriminate between the current models of large scale structure formation.…”
Section: Introductionmentioning
confidence: 78%
“…The isothermal gas parameters in Coma have been determined from an analysis of ROSAT and GINGA data (Briel, Henry, and Böhringer 1992) Recent observations of the intrinsic CMB anisotropies on angular scales ∼0. • 5 (Paper I, Cheng et al 1996, Devlin et al 1994, Netterfield et al 1996 are showing ∆T /T ∼ 2 × 10 −5 . This intrinsic level represents a potentially significant contaminant to SZ observations at these angular scales because the CMB fluctuations may be comparable to the expected signal from the SZ effect.…”
Section: Discussionmentioning
confidence: 96%